Immersive Learning in Construction and Civil Engineering Education - Nguyen, Quan; Dao, Thuy-Ninh; Pham, Thuy-Binh; Aziz, Zeeshan (International Journal of Sustainable Construction Engineering and Technology, 2025)
Immersive learning has gained increasing attention in construction and civil engineering education as institutions confront the demands of Industry 4.0 and the learning preferences of Generation Z. Although virtual, augmented, mixed, and extended reality (VR/AR/MR/XR) technologies have demonstrated strong potential to enhance experiential, interactive, and scenario-based instruction, their adoption remains fragmented and underdeveloped - particularly in developing countries such as Vietnam. This study conducts a PRISMA-guided systematic review of 33 peer-reviewed publications to examine global applications of immersive learning in construction and civil engineering higher education. The findings reveal six dominant thematic domains: safety and hazard recognition, design and visualization, construction methods and procedures, project management and collaboration, robotics and equipment training, and energy and environmental simulation. Building on these themes, the study proposes the Immersive Learning Integration Framework for Construction and Civil Engineering Education (ILIF-CEE), which organizes immersive learning into five dimensions: learning objectives, technology types, interaction and immersion mechanisms, learning outcomes, and implementation enablers and barriers. The framework provides a structured foundation for integrating immersive tools into AEC curricula and for supporting institutional digital-transformation strategies. The study contributes consolidated evidence based on the reviewed publications, identifies critical challenges, and outlines practical implications for educators and policymakers seeking to adopt immersive learning.